URGENSI PENDIDIKAN ANAK SEJAK USIA DINI PADA WILAYAH PESISIR DESA BONEATERO BARAT - Henny Henny; Kadar Risman; Asma Kurniati; Marwah Marwah; Viona Viona (Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2023)
This community service implementation activity is carried out in the coastal area of West Boneatero Village with the aim of implementing the Muhammadiyah university chessdarma. This activity helps the community to solve various educational problems. The main problem that occurs in this area is the increasing dropout rate of children from an early age. The implementation of this activity is targeted at parents to understand the urgency of education itself. The method carried out in this activity is in the form of providing education, question and answer discussions. The result of this civics activity is to help parents understand the importance of providing children's education from an early age and know various daily activities that have educational value for early childhood in coastal areas